Extraction, content determination, component analysis, and pharmacological action of Hedysari flavonoids: a review of research progress - Huang, Cancan; Mao, Haiyan; Wan, Wenwen; Ren, Chunzhen; Ji, Xiujia; Yue, Bin; Zhang, Xiaohua; Wu, Quansheng (Frontiers in Pharmacology, 2025)
Radix Hedysari is a traditional Chinese herbal medicine and food. It has a long history of clinical application and is used to improve health and treat various diseases. Hedysari polysaccharides, flavonoids, saponins, and alkaloids are the main components of Radix Hedysari. Hedysari flavonoids are the most important natural active ingredients in Radix Hedysari and have a variety of pharmacological effects. At present, Hedysari flavonoids have shown great application prospects in the development of drugs for the treatment of pulmonary fibrosis, osteoporosis, skeletal muscle injury, atherosclerosis, hepatic fibrosis, immune regulation, hypoglycemia, and renal fibrosis. This paper reviewed the extraction, separation, and content determination methods and chemical constituents of flavonoids from Radix Hedysari. The core electronic databases used for literature retrieval included Baidu Literature, Baidu Literature, WangFang Datas, CNKI, VIP Datas, PubMed, Google Scholar, and Web of Science. “Radix Hedysari”, “Hong qi”, “Flavonoid”, “Hedysari Flavonoids” and “pharmacological effects”, “extraction” and “structure” were used as the search terms from database creation to 30 October 2024. Multiple studies have shown that Radix Hedysari flavonoids have important pharmacological effects, such as cytotoxic effects on tumor cells, by inhibiting tumor cell growth, inducing tumor cell apoptosis, and enhancing immune function. The antioxidant effect, through the regulation of LDH, SOD, malondialdehyde and other enzymes and the expression of antioxidant-related factors, can improve osteoporosis by promoting osteoblast proliferation and differentiation, reducing calcium loss, increasing bone mineral density, maintaining bone balance and improving bone quality. These effects include reducing oxidation; preventing thrombosis; enhancing endothelial function; regulating blood lipid levels to improve anti-atherosclerosis, anti-pulmonary fibrosis and liver fibrosis performance; improving atherosclerosis; reducing skeletal muscle damage; and exerting immunomodulatory effects, such as regulating various cytokines, immune cells, immune organs and related signaling pathways. This work provides a theoretical foundation for further studies on the structure, mechanism and clinical application of Radix Hedysari flavonoids.